Avaliação e caracterização da qualidade da carne de peito (Pectoralis major)de matrizes pesadas em final de ciclo produtivo - Sanfelice, Cristiane [UNESP]; Mendes, Ariel Antonio [UNESP]; Komiyama, Claudia Marie [UNESP]; Cañizares, Marleide da Costa [UNESP]; Rodrigues, Luciana [UNESP]; Cañizares, Gil Ignácio [UNESP]; Roça, Roberto de Oliveira [UNESP]; Almeida, Ibiara Correia Lima Paz [UNESP]; Balog, Augusto [UNESP]; Milbradt, Elisane Lenita [UNESP]; Cardoso, Karen Franco de Godoy [UNESP] (My University, 2010)
The objective of this study was to evaluate the meat quality characteristics in broiler breeder hen. For this purpose, 40 breast fillet samples (Pectoralis major) of breeder hen, Ross strain with 68 and 69 weeks of age, were collected. The samples were collected twice, and each time twenty samples were obtained. At zero time, (after chilling time) the pH was measured and fragmented samples were collected to evaluate the R value it. At 4 and 24 hours post-mortem, the following analyses were performed: pH, R-value, color, drip loss, water holding capacity (WHC), water absorption capacity (WAC), cooking loss, and shear force. There was a significant difference (p < 0.05) in the average pH values in the zero time (after chilling), 4, and 24 hours, 6.49; 5.78, and 5.65, respectively. The average value of WHC was 26.45. With respect to the objective color, the average values obtained for L*, a*, and b* were 52.20; 3.64; 0.51; respectively. Therefore, it can be concluded that the results obtained for drip loss, cooking loss, and water absorption capacity indicate that the breast meat of breeder hens presented very good technological quality despite its texture problems.
Evaluation and characterization of breast quality of broiler breeder hen in the end of productive cycle
Keywords: Breeder hen; Pectoralis major; Spend hen; Tenderness and color